(untitled) (Itinera, 2020)
The relationship between music and language is one of the main axes of Western philosophy of music. In particular, the link between music and literature has fostered an intense debate that resulted in a plurality of different solutions. The present issue of "Itinera” aims at analyzing some of the fundamental questions that emerge from Azio Corghi’s use of literary sources in composition. The complexity of the themes that characterize Corghi’s work, across musicology, aesthetics and literature, leads the reader to deal with fundamental categories such as postmodernity and avant-garde, in music and beyond.